2017
DOI: 10.1684/epd.2017.0897
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy? Things are not always what they seem

Abstract: Temporal lobe epilepsy is the most frequent form of drug‐resistant epilepsy referred to epilepsy surgery centres. The vast majority of lesional cases can be operated on without invasive investigation which is often not the case for non‐lesional cases. Invasive investigation in non‐lesional cases, however, may lead to unexpected results, as illustrated in the following case report. [Published with video sequence on http://www.epilepticdisorders.com]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Reports of PMC seizures have been rare in the literature (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Bancaud and Talairach (27) were the first to describe a typical syndrome characterized by a "incomplete loss of consciousness" attributed to possible posterior cingulate epilepsy.…”
Section: Significancementioning
confidence: 99%
“…Reports of PMC seizures have been rare in the literature (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Bancaud and Talairach (27) were the first to describe a typical syndrome characterized by a "incomplete loss of consciousness" attributed to possible posterior cingulate epilepsy.…”
Section: Significancementioning
confidence: 99%
“…It would be preferable to run this analysis on a dataset with more complete and uniform coverage of the brain but there are several factors making this difficult. Medial temporal lobe, particularly the areas around the amygdala and the hippocampus, are common locations of seizure onset and, therefore, more frequently targeted ( Irena et al., 2017 ). The small number of centers that do this kind of recordings makes it difficult to create a more comprehensive multi-center dataset as has been done for intracranial recordings alone ( Trebaul et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complex motor behaviours may also be observed in the latecourse of posterior cortex seizures, once the seizure propagates to more anterior regions [1].In the present study,the most common clinical characteristics of complex motor behaviours were exploratory gaze movements and bilateral hand fumbling movements. In these patients, complex motor behaviours were observed only when ictal activity assessed by SEEG had spread to the precuneus, MCC, medial temporal lobe and superior temporal gyrus [12,16].The cingulum bundle was predominantly composed of cingulate bres that head in either a rostral or caudal direction, with the majority bifurcating to go in both directions.The PCG interlinks medial parts of the frontal, parietal, and temporal lobes by the cingulum bundle [17].The highest number of active sites was found in the ventral and dorsal aMCC, whose stimulation triggered a variety of goal-oriented behavioursinvolvingreaching and grasping actions and exploratory gaze movements [11].Therefore, the clinical characteristics of posterior cingulate epilepsy vary among patients that are different from the mesial-temporal lobe epilepsy [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand,the posterior cingulate cortex is known to project to the hippocampus via the entorhinal and parahippocampal cortex and to receive direct and indirect connections from the hippocampus.The inferior cingulum bundle is a white matter tract projecting from the PCC to the hippocampus or parahippocampus and the entorhinal cortex [21,22]. Ictal propagation to the cingulate gyrus has frequently been observed among patients with temporallobe epilepsy [18].However,YCShih found in patients with left mesial temporal lobe epilepsy with hippocampal sclerosis, the left inferior cingulum bundle underwent degeneration in tandem with the left hippocampus volume, whereas intrinsic functional connectivity seems to react by compensating for the loss of connectivity. Their results suggested that increased intrinsic functional connectivity of the contralesional hippocampus was a compensatory response to decreased hippocampal connectivity on the lesion side [23].According to the hypothesis, we speculate that the PCG lesion and hippocampus functional connectivity decreased,but the contralesional PCG and hippocampus have extensive unctional connections.…”
Section: Discussionmentioning
confidence: 99%